Formation of Competences in the Field of Information Security for Future Bachelors of Applied Informatics - I. V. Gavrilova; M. V. Romanova; E. V. Chernova (Открытое образование (Москва))
The purpose of the study is to develop a model for developing competencies in the field of information security for bachelors in the field of Applied Information Science. The relevance of this problem is determined by modern requirements for enterprise employees and, accordingly, the process of their training. Demand for qualified employees who have skills not only in their field of activity, but also in areas relevant to the information society, such as information culture and the ability to provide an information enterprise.Materials and research methods. To achieve this goal, a competency-based approach was used to activate the process of developing the readiness and ability of subjects to make independent decisions, express independent judgments and at the same time participate in a common cause, create relationships with other participants in joint activities. The following methods were used in the work: analysis of pedagogical, scientific, technical and methodological literature on the research problem, systematization and generalization and visual presentation of the results.Results. As part of the study, a tabular model for the formation of competencies in the field of information security was developed based on the competency-based approach. The article reflects a model for developing competence in the field of information security using the example of additional professional competencies - 2 (the ability to take part in project management, organizing IT infrastructure and information security management) in the process of studying the discipline “Information Security”. The component blocks of the developed model are described: diagnostic, motivational, theoretical, practical and control-analytical. In accordance with the stages of this process of developing competencies and the tasks to be solved at each stage, various innovative forms and methods are presented. The results of the paper show that the process of developing competencies in the field of information security among bachelors in the “Applied Information Science” area is complex and multifaceted. Even though bachelors of applied computer science will not perform the same job functions as information security specialists, their training should be sufficient to enable them to design and build safe and reliable information systems. The pedagogical search is not completed, but it has acquired the necessary boundaries, unique centers of crystallization around which the academic discipline is designed.Conclusion. We can conclude that training specialists in the field of information security is an urgent task of modern society, the solution of which is dependent on scientific justification and identification of a set of necessary competencies that a modern specialist should have. The components of competencies in the field of information security that we have identified, the generalized tabular model of these competencies that we have proposed, as well as the stages, methods and forms of developing these competencies among bachelors of Applied Information Science require additional study. The conducted research allows us to outline ways to solve the multifaceted and complex problem of forming students’ competencies in the field of information security, taking into account modern requirements for the training of specialists not only in the field of computer science and information technology.